Anti-fog high-barrier food preservative film and preparation method and application thereof

By adopting a multi-layer structure design in food plastic wrap, combined with orange peel particles, sodium alginate and other ingredients, the problem of insufficient performance of food plastic wrap in the existing technology is solved, and efficient anti-fog, barrier, antibacterial and anti-aging is achieved. The oxidation effect extends the shelf life of food.

CN118930938BActive Publication Date: 2024-12-20CHENGDU UNIV +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411427160.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-20
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

Existing food plastic wrap is difficult to take into account anti-fog performance, barrier properties, antibacterial properties and antioxidant properties, and food waste is not used as raw materials.

Method used

Design of food plastic wrap with multi-layer structure, including base layer, surface spray self-assembly layer and coating layer, by combining orange peel particles, sodium alginate, chitosan, orange peel water extract, lemon peel water extract and Combining ingredients such as glutamine transaminase gelatin form a thin film material with excellent anti-fog, barrier, antibacterial and antioxidant properties.

Benefits of technology

It has achieved high antibacterial properties, excellent anti-fog performance, low oxygen permeability and high oxidation resistance, significantly extending the shelf life of food.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the technical field of multilayer materials. The present invention provides an anti-fog high-barrier food preservative film, a preparation method thereof and an application thereof. The provided anti-fog high-barrier food preservative film is a multilayer structure, consisting of a base layer, two surface spray self-assembly layers and two coating layers. The base layer is made of orange peel powder particles placed in a low-density polyethylene solution, the surface spray layer is made of sodium alginate and chitosan containing tartaric acid, and the coating layer is made of orange peel water extract, lemon peel water extract, glutamine transaminase and gelatin. The food preservative film provided by the present invention has excellent anti-fog performance, barrier performance, antibacterial performance and antioxidant performance, and can significantly improve the preservation effect of food.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of multilayer materials, and relates to a multilayer food cling film material, and in particular to an anti-fog high-barrier food cling film and a preparation method and application thereof. Background Art

[0002] At present, food cling film has been widely used in all aspects of people's lives. However, the existing food cling film still has various deficiencies, such as poor anti-fog performance, insufficient antibacterial and antioxidant properties, and poor barrier properties.

[0003] Traditional plastic food cling film materials are mainly polyethylene film (PE film) and polyvinyl chloride film (PVP film), which have certain barrier properties and have been widely used as packaging materials for various foods. However, this type of cling film often lacks antibacterial, anti-fogging and high barrier properties, resulting in poor preservation of fresh products such as fruits and vegetables that have a respiratory effect.

[0004] In the preparation of anti-fog cling film, people have studied the use of co-extrusion to prepare multi-layer anti-fog films, such as Shen Long et al. [1] The application and anti-fog performance of multi-layer co-extruded films were evaluated; the preparation of multi-layer anti-fog films by adding anti-fog agents was also studied. For example, Tang Hu et al. provided a biaxially oriented polyethylene heat-seal anti-fog film and a preparation method thereof in patent CN113119567B. In addition to adding low-density polyethylene, an anti-fog masterbatch was also added to the core layer.

[0005] In the preparation of antibacterial and antioxidant cling film, people obtain cling film with antibacterial and antioxidant properties by adding relevant antibacterial agents and antioxidants.

[0006] However, as far as the inventors know, existing food cling films often cannot take into account anti-fog performance, barrier performance, antibacterial performance and antioxidant performance. On this basis, food waste is rarely used as raw materials for preparing cling films.

[0007] Therefore, there is an urgent need in the art for a food preservative film that uses food waste as a raw material and has excellent anti-fog performance, barrier performance, antibacterial performance and antioxidant performance. Summary of the invention

[0008] In view of the defects of the prior art, the object of the present invention is to provide a film material having excellent anti-fog performance, barrier performance, antibacterial performance and antioxidant performance, and to use the film material as a food preservative film.

[0009] In order to achieve the above object, the present invention provides the following technical solutions:

[0010] An anti-fog high-barrier food preservative film, the food preservative film is a multi-layer structure, consisting of a base layer, two surface spray self-assembly layers and two coating layers;

[0011] The base layer is arranged in the middle of the thickness direction of the cling film, the two surface spray layers are arranged on the two surfaces of the base layer respectively, and the two coating layers are arranged on the outer surfaces of the two surface spray layers respectively;

[0012] The base layer is a low-density polyethylene film layer, which is formed by placing orange peel particles in a low-density polyethylene solution for casting. The particle size of the orange peel particles is 50-100 μm, and the amount of the orange peel particles added is 5-8% of the weight of the low-density polyethylene.

[0013] The surface spray self-assembled layer is prepared by spraying a sodium alginate solution containing tartaric acid on a substrate layer by electrostatic spraying to obtain a sodium alginate spray surface; then spraying a chitosan solution containing tartaric acid on the sodium alginate spray surface by electrospraying, and then drying to obtain a surface spray self-assembled layer; in the sodium alginate solution, the solvent is water, the weight percentage of sodium alginate is 3-5%; the amount of tartaric acid added is 1-2% of the weight of sodium alginate; in the chitosan solution, the solvent is a mixture of acetic acid and water in a volume ratio of 7:4, the weight percentage of chitosan is 1-2%, and the amount of tartaric acid added is 1-2% of the weight of chitosan;

[0014] The coating layer is obtained by coating a gelatin solution containing tangerine peel water extract, lemon peel water extract and glutamine transaminase on a surface spray layer and drying the solution, wherein the weight ratio of the tangerine peel water extract, lemon peel water extract and glutamine transaminase is 15-20:5-8:1; in the gelatin solution, the solvent is water, the weight percentage of gelatin is 5-6%, and the amount of tangerine peel water extract added is 3-5% of the weight of gelatin.

[0015] Preferably, the added amount of the orange peel particles is 6% by weight of the low-density polyethylene.

[0016] Preferably, in the sodium alginate solution, the solvent is water, and the weight percentage of sodium alginate is 4%; the amount of tartaric acid added is 1.5% of the weight of sodium alginate; in the chitosan solution, the solvent is a mixture of acetic acid and water in a volume ratio of 7:4, the weight percentage of chitosan is 2%, and the amount of tartaric acid added is 1.5% of the weight of chitosan.

[0017] Preferably, the weight ratio of the tangerine peel water extract, lemon peel water extract and glutamine transaminase is 18:6:1, the solvent in the gelatin solution is water, the weight percentage of gelatin is 6%, and the added amount of the tangerine peel water extract is 4% of the weight of the gelatin.

[0018] Preferably, in the surface spray self-assembled layer, the weights of sodium alginate and chitosan are consistent; and the thickness ratio of the base layer, the surface spray self-assembled layer and the coating layer is 3:1:1.

[0019] Preferably, the preparation method of the tangerine peel water extract is: wash and chop the tangerine peel, add water according to the weight ratio of tangerine peel to water of 1:10, soak overnight, boil twice, each time for 1 hour, filter and combine the filtrate, concentrate the filtrate to an extract, and then freeze-dry the extract into powder.

[0020] Preferably, the preparation method of the lemon peel water extract is: wash and chop the lemon peel, add water according to the weight ratio of lemon peel to water of 1:10, soak overnight, decoct twice, each time for 1 hour, filter and combine the filtrate, concentrate the filtrate to an extract, and then freeze-dry the extract into powder.

[0021] Another object of the present invention is to provide a method for preparing the above-mentioned anti-fog high-barrier food cling film, wherein the food cling film is the above-mentioned anti-fog high-barrier food cling film; the preparation method comprises the following steps:

[0022] (1) dissolving low-density polyethylene in chloroform to form a solution of 3 to 5 g / L, adding the orange peel particles and mixing them thoroughly, casting them into a culture dish, and drying them in a forced air dryer at 55° C. for 6 hours to obtain a base layer;

[0023] (2) spraying the sodium alginate solution containing tartaric acid onto one surface of the substrate layer by electrostatic spraying, with a voltage of 20 KV, an injection speed of 1 mL / h, and a needle size of 25G, to form a sodium alginate spray surface, and then spraying the chitosan solution containing tartaric acid onto the sodium alginate spray surface by electrospraying, with a voltage of 18 KV, an injection speed of 0.5 mL / h, and a needle size of 18G, to form a surface spray self-assembled layer; and then treating the other surface of the substrate layer in the same manner to obtain another surface spray self-assembled layer;

[0024] (3) The orange peel water extract, lemon peel water extract, glutamine aminotransferase and gelatin are dissolved in water, and then uniformly coated on the outer surfaces of the two surface spray self-assembled layers respectively, and then dried in a forced air dryer at 55° C. for 6 hours to obtain two coating layers.

[0025] Preferably, in the surface spray self-assembled layer, the weights of sodium alginate and chitosan are consistent; the thickness of the base layer is 0.03 mm, and the thickness ratio of the base layer, the surface spray self-assembled layer and the coating layer is 3:1:1.

[0026] Another object of the present invention is to provide an application of the above-mentioned anti-fog high-barrier food preservative film as a food preservative film, wherein the food includes peaches.

[0027] Beneficial effects of the present invention:

[0028] The anti-fog high-barrier food preservative film obtained by the present invention has high antibacterial property, the antibacterial rate for Escherichia coli reaches 99%, and the antibacterial rate for Staphylococcus aureus reaches more than 95%; it also has excellent anti-fog performance, and after cold treatment, the change range of light transmittance is small; it also has excellent oxygen barrier property, and the oxygen permeability can be as low as 15.0mL / m 2 • day • 0.1MPa; it also has excellent antioxidant properties, and the removal rate of DPPH free radicals can reach more than 98%. The anti-fog high-barrier food preservative film obtained by the invention has a good preservation effect on food and can significantly extend the shelf life of food. DETAILED DESCRIPTION

[0029] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technical personnel in this field based on the above invention content still fall within the scope of protection of the present invention.

[0030] The raw materials used in the following examples and comparative examples are:

[0031] Orange peel: dried peel of commercially available orange (Yunnan mandarin orange);

[0032] Orange peel particles: dried peel powder of commercially available oranges (Yunnan mandarin oranges), with a particle size of 50-100 μm;

[0033] Lemon peel: dried peel of commercial lemon (citrus limon);

[0034] Low-density polyethylene: Shanghai Qiaowei Chemical Technology Co., Ltd., brand: LL0220K;

[0035] Sodium alginate: Jiangsu Fushengde Bioengineering Co., Ltd., food grade, product number: 102;

[0036] Chitosan: Guangzhou Huaxi Bioengineering Co., Ltd., food grade, product number: 101;

[0037] Tartaric acid: Henan Youchuang Chemical Products Co., Ltd., DL-tartaric acid;

[0038] Gelatin: Xi'an Lavia Biotechnology Co., Ltd., food grade;

[0039] Glutamine transaminase: Sigma-Aldrich;

[0040] Acetic acid, ultrapure water: laboratory-owned;

[0041] Peaches: available in local market;

[0042] Tangerine peel water extract: Wash and chop the tangerine peel, add water according to the weight ratio of tangerine peel to water of 1:10, soak overnight, boil twice, 1 hour each time, filter and combine the filtrate, concentrate the filtrate to an extract, and then freeze-dry the extract into powder.

[0043] Lemon peel water extract: Wash and chop the lemon peel, add water according to the weight ratio of lemon peel to water of 1:10, soak overnight, boil twice, 1 hour each time, filter and combine the filtrate, concentrate the filtrate to an extract, and then freeze-dry the extract into powder.

[0044] Example 1

[0045] (1) Low-density polyethylene was dissolved in chloroform to form a 4 g / L solution, and orange peel particles were added and mixed thoroughly (the amount of orange peel particles added was 6% of the weight of low-density polyethylene), and cast into a culture dish, and dried in a blast dryer at 55° C. for 6 hours to obtain a film with a thickness of 0.03 mm as a base layer;

[0046] (2) Add tartaric acid and sodium alginate to water to prepare an aqueous solution with a sodium alginate weight percentage of 4%, and make the added amount of tartaric acid be 1.5% of the weight of sodium alginate; spray the prepared sodium alginate solution containing tartaric acid on one surface of the substrate by electrostatic spraying to form a sodium alginate spray surface; when performing electrostatic spraying, the voltage is 20KV, the injection speed is 1mL / h, and the needle size is 25G;

[0047] (3) Adding tartaric acid and chitosan to an acetic acid aqueous solution (the volume ratio of acetic acid to water is 7:4) to prepare a solution with a chitosan weight percentage of 2%, and the amount of tartaric acid added is 1.5% of the weight of chitosan; after the above solution is prepared, immediately spraying the above solution on the sodium alginate spray surface obtained in step (2) by electrospraying, and the voltage during electrostatic spraying is 18KV, the injection speed is 0.5mL / h, and the needle size is 18G; through steps (2) and (3), a surface spray self-assembled layer is formed, the thickness of the layer is 0.01mm, and the weight of chitosan and sodium alginate is consistent;

[0048] (4) The method of step (2) and step (3) is used to treat another surface of the substrate layer to obtain another surface spray self-assembled layer;

[0049] (5) Orange peel water extract, lemon peel water extract and glutamine aminotransferase were prepared in a weight ratio of 18:6:1, and then dissolved in water together with gelatin so that the weight percentage of gelatin was 6% and the amount of orange peel water extract added was 4% of the weight of gelatin; the obtained solutions were uniformly coated on the outer surfaces of the obtained two layers of surface spray self-assembled layers, and then dried in a blower dryer at 55°C for 6 hours to obtain two coating layers, each of which had a thickness of 0.01 mm.

[0050] Example 2

[0051] (1) Low-density polyethylene was dissolved in chloroform to form a 5 g / L solution, and orange peel particles were added and mixed thoroughly (the amount of orange peel particles added was 5% of the weight of low-density polyethylene), and then cast into a culture dish, and dried in a blast dryer at 55°C for 6 hours to obtain a film with a thickness of 0.03 mm as a base layer;

[0052] (2) Add tartaric acid and sodium alginate into water to prepare an aqueous solution with a sodium alginate weight percentage of 5%, and make the added amount of tartaric acid be 1% of the weight of sodium alginate; spray the prepared sodium alginate solution containing tartaric acid onto one surface of the substrate layer by electrostatic spraying to form a sodium alginate spray surface; when performing electrostatic spraying, the voltage is 20KV, the injection speed is 1mL / h, and the needle size is 25G;

[0053] (3) Adding tartaric acid and chitosan to an acetic acid aqueous solution (the volume ratio of acetic acid to water is 7:4) to prepare a solution with a chitosan weight percentage of 1%, and making the amount of tartaric acid added be 2% of the weight of chitosan; after the above solution is prepared, immediately spraying the above solution onto the sodium alginate spray surface obtained in step (2) by electrospraying, and during the electrostatic spraying, the voltage is 18KV, the injection speed is 0.5mL / h, and the needle size is 18G; through steps (2) and (3), a layer of surface spray self-assembled layer is formed, the thickness of the layer is 0.01mm, and the weight of chitosan and sodium alginate is the same;

[0054] (4) The method of step (2) and step (3) is used to treat another surface of the substrate layer to obtain another surface spray self-assembled layer;

[0055] (5) Orange peel water extract, lemon peel water extract and glutamine aminotransferase were prepared in a weight ratio of 20:5:1, and then dissolved in water together with gelatin so that the weight percentage of gelatin was 5% and the amount of orange peel water extract added was 3% of the weight of gelatin; the obtained solutions were uniformly coated on the outer surfaces of the obtained two layers of surface spray self-assembled layers, and then dried in a blower dryer at 55°C for 6 hours to obtain two coating layers, each of which had a thickness of 0.01 mm.

[0056] Example 3

[0057] (1) Low-density polyethylene was dissolved in chloroform to form a 3 g / L solution, and orange peel particles were added and mixed thoroughly (the amount of orange peel particles added was 8% of the weight of low-density polyethylene), and cast into a culture dish, and dried in a blast dryer at 55° C. for 6 hours to obtain a film with a thickness of 0.03 mm as a base layer;

[0058] (2) Add tartaric acid and sodium alginate into water to prepare an aqueous solution with a sodium alginate weight percentage of 3%, and make the added amount of tartaric acid be 2% of the weight of sodium alginate; spray the prepared sodium alginate solution containing tartaric acid onto one surface of the substrate layer by electrostatic spraying to form a sodium alginate spray surface; when performing electrostatic spraying, the voltage is 20KV, the injection speed is 1mL / h, and the needle size is 25G;

[0059] (3) Adding tartaric acid and chitosan to an acetic acid aqueous solution (the volume ratio of acetic acid to water is 7:4) to prepare a solution with a chitosan weight percentage of 1.5%, and making the amount of tartaric acid added be 1% of the weight of chitosan; after the above solution is prepared, immediately spraying the above solution onto the sodium alginate spray surface obtained in step (2) by electrospraying, and during the electrostatic spraying, the voltage is 18KV, the injection speed is 0.5mL / h, and the needle size is 18G; through steps (2) and (3), a layer of surface spray self-assembled layer is formed, the thickness of the layer is 0.01mm, and the weight of chitosan and sodium alginate is the same;

[0060] (4) The method of step (2) and step (3) is used to treat another surface of the substrate layer to obtain another surface spray self-assembled layer;

[0061] (5) Orange peel water extract, lemon peel water extract and glutamine aminotransferase were prepared in a weight ratio of 15:8:1, and then dissolved in water together with gelatin so that the weight percentage of gelatin was 5.5% and the amount of orange peel water extract added was 6% of the weight of gelatin; the obtained solutions were uniformly coated on the outer surfaces of the obtained two layers of surface spray self-assembled layers, and then dried in a blower dryer at 55°C for 6 hours to obtain two coating layers, each of which had a thickness of 0.01 mm.

[0062] Through the above steps (1) to (5), a multilayer thin film material is obtained.

[0063] Comparative Example 1

[0064] Compared with Example 1, this comparative example 1 lacks a coating layer, and the rest is consistent with Example 1. The specific technical scheme is as follows:

[0065] (1) Low-density polyethylene was dissolved in chloroform to form a 4 g / L solution, and orange peel particles were added and mixed thoroughly (the amount of orange peel particles added was 6% of the weight of low-density polyethylene), and cast into a culture dish, and dried in a blast dryer at 55° C. for 6 hours to obtain a film with a thickness of 0.03 mm as a base layer;

[0066] (2) Add tartaric acid and sodium alginate to water to prepare an aqueous solution with a sodium alginate weight percentage of 4%, and make the added amount of tartaric acid be 1.5% of the weight of sodium alginate; spray the prepared sodium alginate solution containing tartaric acid on one surface of the substrate by electrostatic spraying to form a sodium alginate spray surface; when performing electrostatic spraying, the voltage is 20KV, the injection speed is 1mL / h, and the needle size is 25G;

[0067] (3) Adding tartaric acid and chitosan to an acetic acid aqueous solution (the volume ratio of acetic acid to water is 7:4) to prepare a solution with a chitosan weight percentage of 2%, and the amount of tartaric acid added is 1.5% of the weight of chitosan; after the above solution is prepared, immediately spraying the above solution on the sodium alginate spray surface obtained in step (2) by electrospraying, and the voltage during electrostatic spraying is 18KV, the injection speed is 0.5mL / h, and the needle size is 18G; through steps (2) and (3), a surface spray self-assembled layer is formed, the thickness of the layer is 0.01mm, and the weight of chitosan and sodium alginate is consistent;

[0068] (4) The method of step (2) and step (3) is used to treat another surface of the substrate layer to obtain another surface spray self-assembled layer.

[0069] Through the above steps (1) to (4), a multilayer thin film material is obtained.

[0070] Comparative Example 2

[0071] Compared with Example 1, this comparative example lacks a surface spray self-assembly layer, and the rest is consistent with Example 1. The specific technical scheme is as follows:

[0072] (1) Low-density polyethylene was dissolved in chloroform to form a 4 g / L solution, and orange peel particles were added and mixed thoroughly (the amount of orange peel particles added was 6% of the weight of low-density polyethylene), and cast into a culture dish, and dried in a blast dryer at 55° C. for 6 hours to obtain a film with a thickness of 0.03 mm as a base layer;

[0073] (2) orange peel water extract, lemon peel water extract and glutamine aminotransferase were prepared in a weight ratio of 18:6:1, and then dissolved in water together with gelatin so that the weight percentage of gelatin was 6% and the amount of orange peel water extract added was 4% of the weight of gelatin; the obtained solutions were evenly coated on the two surfaces of the obtained base layer, and then dried in a blower dryer at 55°C for 6 hours to obtain two coating layers, each of which had a thickness of 0.01 mm.

[0074] Through the above steps (1) to (2), a multilayer thin film material is obtained.

[0075] Comparative Example 3

[0076] Compared with Example 1, this comparative example lacks tartaric acid, and the rest is consistent with Example 1. The specific technical scheme is as follows:

[0077] (1) Low-density polyethylene was dissolved in chloroform to form a 4 g / L solution, and orange peel particles were added and mixed thoroughly (the amount of orange peel particles added was 6% of the weight of low-density polyethylene), and cast into a culture dish, and dried in a blast dryer at 55° C. for 6 hours to obtain a film with a thickness of 0.03 mm as a base layer;

[0078] (2) adding sodium alginate to water to prepare an aqueous solution with a weight percentage of sodium alginate of 4%; spraying the prepared sodium alginate solution onto one surface of the substrate layer by electrostatic spraying to form a sodium alginate spray surface; during the electrostatic spraying, the voltage is 20KV, the injection speed is 1mL / h, and the needle size is 25G;

[0079] (3) adding chitosan to an acetic acid aqueous solution (the volume ratio of acetic acid to water is 7:4) to prepare a solution with a chitosan weight percentage of 2%; spraying the prepared chitosan solution onto the sodium alginate spray surface obtained in step (2) by electrospraying, wherein the voltage is 18KV, the injection speed is 0.5mL / h, and the needle size is 18G during electrostatic spraying; forming a surface spray self-assembled layer through steps (2) and (3), the thickness of the layer is 0.01mm, and the weight of chitosan and sodium alginate is consistent;

[0080] (4) The method of step (2) and step (3) is used to treat another surface of the substrate layer to obtain another surface spray self-assembled layer;

[0081] (5) Orange peel water extract, lemon peel water extract and glutamine aminotransferase were prepared in a weight ratio of 18:6:1, and then dissolved in water together with gelatin so that the weight percentage of gelatin was 6% and the amount of orange peel water extract added was 4% of the weight of gelatin; the obtained solutions were uniformly coated on the outer surfaces of the obtained two layers of surface spray self-assembled layers, and then dried in a blower dryer at 55°C for 6 hours to obtain two coating layers, each of which had a thickness of 0.01 mm.

[0082] Through the above steps (1) to (5), a multilayer thin film material is obtained.

[0083] Comparative Example 4

[0084] Compared with Example 1, this comparative example is different in that lemon peel water extract is missing, and the rest is consistent with Example 1. The specific technical scheme is as follows:

[0085] (1) Low-density polyethylene was dissolved in chloroform to form a 4 g / L solution, and orange peel particles were added and mixed thoroughly (the amount of orange peel particles added was 6% of the weight of low-density polyethylene), and cast into a culture dish, and dried in a blast dryer at 55° C. for 6 hours to obtain a film with a thickness of 0.03 mm as a base layer;

[0086] (2) Add tartaric acid and sodium alginate to water to prepare an aqueous solution with a sodium alginate weight percentage of 4%, and make the added amount of tartaric acid be 1.5% of the weight of sodium alginate; spray the prepared sodium alginate solution containing tartaric acid on one surface of the substrate by electrostatic spraying to form a sodium alginate spray surface; when performing electrostatic spraying, the voltage is 20KV, the injection speed is 1mL / h, and the needle size is 25G;

[0087] (3) Adding tartaric acid and chitosan to an acetic acid aqueous solution (the volume ratio of acetic acid to water is 7:4) to prepare a solution with a chitosan weight percentage of 2%, and the amount of tartaric acid added is 1.5% of the weight of chitosan; after the above solution is prepared, immediately spraying the above solution on the sodium alginate spray surface obtained in step (2) by electrospraying, and the voltage during electrostatic spraying is 18KV, the injection speed is 0.5mL / h, and the needle size is 18G; through steps (2) and (3), a surface spray self-assembled layer is formed, the thickness of the layer is 0.01mm, and the weight of chitosan and sodium alginate is consistent;

[0088] (4) The method of step (2) and step (3) is used to treat another surface of the substrate layer to obtain another surface spray self-assembled layer;

[0089] (5) Prepare tangerine peel water extract and glutamine transaminase in a weight ratio of 18:1, and then dissolve them in water together with gelatin so that the weight percentage of gelatin is 6% and the amount of tangerine peel water extract added is 4% of the weight of gelatin; the obtained solutions are uniformly coated on the outer surfaces of the obtained two layers of surface spray self-assembled layers, and then dried in a blower dryer at 55°C for 6 hours to obtain two coating layers, each of which has a thickness of 0.01 mm.

[0090] Through the above steps (1) to (5), a multilayer thin film material is obtained.

[0091] Comparative Example 5

[0092] The difference between this comparative example and Example 1 is that glutamine aminotransferase is missing, and the rest is consistent with Example 1. The specific technical scheme is as follows:

[0093] (1) Low-density polyethylene was dissolved in chloroform to form a 4 g / L solution, and orange peel particles were added and mixed thoroughly (the amount of orange peel particles added was 6% of the weight of low-density polyethylene), and cast into a culture dish, and dried in a blast dryer at 55° C. for 6 hours to obtain a film with a thickness of 0.03 mm as a base layer;

[0094] (2) Add tartaric acid and sodium alginate to water to prepare an aqueous solution with a sodium alginate weight percentage of 4%, and make the added amount of tartaric acid be 1.5% of the weight of sodium alginate; spray the prepared sodium alginate solution containing tartaric acid on one surface of the substrate by electrostatic spraying to form a sodium alginate spray surface; when performing electrostatic spraying, the voltage is 20KV, the injection speed is 1mL / h, and the needle size is 25G;

[0095] (3) Adding tartaric acid and chitosan to an acetic acid aqueous solution (the volume ratio of acetic acid to water is 7:4) to prepare a solution with a chitosan weight percentage of 2%, and the amount of tartaric acid added is 1.5% of the weight of chitosan; after the above solution is prepared, immediately spraying the above solution on the sodium alginate spray surface obtained in step (2) by electrospraying, and the voltage during electrostatic spraying is 18KV, the injection speed is 0.5mL / h, and the needle size is 18G; through steps (2) and (3), a surface spray self-assembled layer is formed, the thickness of the layer is 0.01mm, and the weight of chitosan and sodium alginate is consistent;

[0096] (4) The method of step (2) and step (3) is used to treat another surface of the substrate layer to obtain another surface spray self-assembled layer;

[0097] (5) Orange peel water extract and lemon peel water extract were prepared in a weight ratio of 18:6, and then dissolved in water together with gelatin so that the weight percentage of gelatin was 6% and the amount of orange peel water extract added was 4% of the weight of gelatin; the obtained solutions were uniformly coated on the outer surfaces of the obtained two layers of surface spray self-assembled layers, and then dried in a blower dryer at 55° C. for 6 hours to obtain two coating layers, each of which had a thickness of 0.01 mm.

[0098] Through the above steps (1) to (5), a multilayer thin film material is obtained.

[0099] Comparative Example 6

[0100] Compared with Example 1, this comparative example is different in that the orange peel particles are missing, and the rest is the same as Example 1. The specific technical scheme is as follows:

[0101] (1) Low-density polyethylene was dissolved in chloroform to form a 4 g / L solution, which was cast into a culture dish and dried in a forced air dryer at 55 °C for 6 hours to obtain a film with a thickness of 0.03 mm as a base layer;

[0102] (2) Add tartaric acid and sodium alginate to water to prepare an aqueous solution with a sodium alginate weight percentage of 4%, and make the added amount of tartaric acid be 1.5% of the weight of sodium alginate; spray the prepared sodium alginate solution containing tartaric acid on one surface of the substrate by electrostatic spraying to form a sodium alginate spray surface; when performing electrostatic spraying, the voltage is 20KV, the injection speed is 1mL / h, and the needle size is 25G;

[0103] (3) Adding tartaric acid and chitosan to an acetic acid aqueous solution (the volume ratio of acetic acid to water is 7:4) to prepare a solution with a chitosan weight percentage of 2%, and the amount of tartaric acid added is 1.5% of the weight of chitosan; after the above solution is prepared, immediately spraying the above solution on the sodium alginate spray surface obtained in step (2) by electrospraying, and the voltage during electrostatic spraying is 18KV, the injection speed is 0.5mL / h, and the needle size is 18G; through steps (2) and (3), a surface spray self-assembled layer is formed, the thickness of the layer is 0.01mm, and the weight of chitosan and sodium alginate is consistent;

[0104] (4) The method of step (2) and step (3) is used to treat another surface of the substrate layer to obtain another surface spray self-assembled layer;

[0105] (5) Orange peel water extract, lemon peel water extract and glutamine aminotransferase were prepared in a weight ratio of 18:6:1, and then dissolved in water together with gelatin so that the weight percentage of gelatin was 6% and the amount of orange peel water extract added was 4% of the weight of gelatin; the obtained solutions were uniformly coated on the outer surfaces of the obtained two layers of surface spray self-assembled layers, and then dried in a blower dryer at 55°C for 6 hours to obtain two coating layers, each of which had a thickness of 0.01 mm.

[0106] Through the above steps (1) to (5), a multilayer thin film material is obtained.

[0107] Experimental Example 1

[0108] In this experimental example, the multilayer film materials obtained in Examples 1 to 3 and Comparative Examples 1 to 6 were subjected to anti-fogging tests. The test method is as follows: the transmittance (wavelength 600nm) of the multilayer film materials obtained in Examples 1 to 3 and Comparative Examples 1 to 6 before being placed in a refrigerator is tested as the initial transmittance, and then a beaker containing peaches is sealed and placed in a -25°C refrigerator for 1 hour before being taken out, and then the transmittance (wavelength 600nm) is tested at room temperature as the cold treatment transmittance, and the transmittance changes before and after the cold treatment are compared. At the same time, a commercially available PE film is used as a control group. The results are shown in Table 1.

[0109] Table 1

[0110]

[0111] As shown in Table 1, by comparing Comparative Example 5 with Example 1, it can be seen that the addition of glutamine aminotransferase has a great effect on the anti-fogging performance of the obtained film. In the prior art, it has been found that enzymes have a modifying effect on gelatin, such as RATHER JA [2] A relatively detailed summary has been made on the modification of gelatin using enzymes. There have been some reports on the modification of gelatin using transglutaminase, but there are relatively few reports on improving the anti-fog performance of films. In particular, as shown in Comparative Example 2 and Comparative Example 6, the anti-fog performance of the films obtained in Examples 1-3 of the present invention is not only due to the modification of gelatin with transglutaminase in the coating layer, but also depends on the presence of the surface spray self-assembled layer and the porous modification of the substrate layer. In addition, as shown in Comparative Example 1, when there is no coating layer, the anti-fog performance of the obtained film material also decreases significantly, and the light transmittance decreases significantly after cold treatment.

[0112] The films obtained in Examples 1-3 maintain good transmittance, which may be due to the porous modification of the substrate layer, so that the surface spray self-assembled layer can be more closely combined with the substrate layer, making the film material more compact as a whole; glutamine aminotransferase modifies gelatin, changes the membrane network between gelatin chains, and closely combines with the surface spray self-assembled layer, and improves the wettability of water to the film as a whole through these aspects. In addition, as shown in Comparative Examples 3 and 4, although the anti-fog performance of the obtained film is reduced, the degree of reduction is not large, and no further analysis is performed.

[0113] Experimental Example 2

[0114] In this experimental example, oxygen permeability test was performed on the multilayer film materials obtained in Examples 1 to 3 and Comparative Examples 1 to 6.

[0115] Oxygen permeability test: The instrument used is an oxygen permeability meter. The membrane is fixed on the workbench. When testing, the upper chamber flow rate of the oxygen permeability meter is set to 20mL / min, and the lower chamber flow rate is set to 10mL / min. Zero point blowing is performed for 2 hours to stabilize the zero point below 5PPM, and the zero point measurement is completed; then the upper chamber flow rate is controlled to 20mL / min, and the test is performed for another 4 hours. According to the test results, the oxygen permeability (mL / m 2 •day•0.1MPa). The commercially available PE film was used as the control group.

[0116] Table 2

[0117]

[0118] Commercially available PE film is a common preservation material, but its barrier property is poor, and its oxygen permeability is usually 1600 mL / m 2 •Day•0.1MPa or more. Low-density polyethylene cling film has a higher oxygen permeability, generally 10,000~20,000 mL / m 2 •Day•0.1MPa.

[0119] As shown in Table 2, when there is no coating layer, the oxygen permeability is significantly reduced compared with the commercially available PE film, but it is still higher than the films made of general materials. For example, the oxygen permeability of polylactic acid film can reach 500mL / m 2 • Day • About 0.1MPa. As shown in Comparative Example 2, Comparative Example 6 and Example 1, the presence of the surface spray self-assembled layer is important for the barrier property. As mentioned above, the reason may be that on the basis of the base layer made of porous low-density polyethylene, the electrostatic spraying is used to achieve a close combination with the base layer, which enhances the barrier property of the obtained film material. As shown in Comparative Example 5 and Example 1, the use of glutamine transaminase to modify gelatin also has a great influence on the barrier property of the obtained film material.

[0120] As shown in Examples 1-3, the film material obtained by the present invention has excellent oxygen barrier properties, which is only 15.0 mL / m 2 •Day•About 0.1MPa.

[0121] Experimental Example 3

[0122] In this example, the antibacterial effect of the multilayer film materials obtained in Examples 1 to 3 and Comparative Examples 1 to 6 was tested with reference to QBT 2591-2003 "Antibacterial Plastics - Antibacterial Performance Test Method and Antibacterial Effect". The experimental results are shown in Table 3.

[0123] Table 3

[0124]

[0125] As shown in Table 3, the film materials obtained in Examples 1 to 3 of the present invention have excellent antibacterial effects, with an antibacterial rate of up to 99% for Escherichia coli and 95% for Staphylococcus aureus. As shown in Comparative Example 1 and Example 1, the coating layer of the present invention is crucial for antibacterial properties, because the coating layer contains orange peel water extract and lemon peel water extract; in addition, as shown in Comparative Example 2, Comparative Example 3 and Example 1, tartaric acid in the surface spray self-assembled layer is also important for antibacterial properties. As shown in Comparative Example 4 and Example 1, the presence or absence of lemon peel water extract also has a great influence on antibacterial properties.

[0126] From the above results, it can be seen that in the present invention, orange peel water extract, lemon peel water extract and tartaric acid have a synergistic effect in antibacterial properties, and are all indispensable components of the film materials with excellent antibacterial properties obtained in Examples 1-3 of the present invention.

[0127] Experimental Example 4

[0128] In this example, the antioxidant properties of the films obtained from the multilayer film materials obtained from Examples 1 to 3 and Comparative Examples 1 to 6 were tested. The test method is as follows: a 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) solution with a concentration of 0.02 mg / mL is prepared with anhydrous ethanol, and the films obtained from each example and comparative example are cut into discs with a diameter of 10 mm, placed in 10 mL of the aforementioned DPPH solution for 30 minutes, and the absorbance values ​​at 517 nm before and after the addition of the discs are measured, and the DPPH scavenging rate is calculated according to the following formula. The results are shown in Table 4.

[0129]

[0130] Table 4

[0131]

[0132] As shown in Table 4, in terms of antioxidant properties, the DPPH free radical scavenging rate of each embodiment and comparative example is similar to the antibacterial property. This indicates that the orange peel water extract, lemon peel water extract and tartaric acid have a synergistic effect in terms of antioxidant properties (DPPH free radicals) in addition to the antibacterial properties. At the same time, as shown in Examples 1-3, the film material obtained by the present invention has excellent antioxidant properties.

[0133] It can be seen from Experimental Examples 1 to 4 that the film material obtained by the present invention has excellent anti-fogging performance, barrier performance, antibacterial performance and antioxidant performance, and is suitable for use as food preservative film.

[0134] In the experiment of Experimental Example 1, the inventors selected peaches as the test fruit. Based on the excellent results obtained in Experimental Examples 2-4, the inventors selected the film material obtained in Example 1 as the plastic wrap for peaches, and used the commercially available PE plastic wrap as the control group. The experimental group and the control group were stored at 4°C for 30 days to examine the respiration intensity, enzyme activity, sugar-acid ratio, hardness, malondialdehyde and other indicators. The experiment found that the respiration intensity of peaches in the experimental group was significantly lower than that of the control group. The peak respiration of the control group was on the 13th day (reaching 68.02 mL·(kg·h) -1 ), while the experimental group delayed the peak of respiratory rate to the 27th day (45.91 mL·(kg·h) -1 After 30 days, the polyphenol oxidase activity in the experimental group was 165 U·g -1 , which was significantly lower than the polyphenol oxidase activity in the control group (342 U·g -1 ); After testing, after 30 days, the sugar-acid ratio of the experimental group was 36.4, significantly higher than that of the control group (21.8); After testing, after 30 days, the firmness of peaches in the experimental group decreased by 14%, while the firmness of peaches in the control group decreased by 50%; After testing, the malondialdehyde content of the experimental group was 0.15μmol˙kg -1 The malondialdehyde content in the control group was 0.66 μmol˙kg -1 It can be seen that the composite nanofilm obtained in Example 1 has a good preservation effect on peaches. The thin film material obtained in Example 1 of the present invention is used as a preservative film for peaches. The peaches are packaged at +4°C for 30 days and still have a good commercial value. This storage method is significantly longer than the traditional 5-day cold storage period and has a better preservation effect.

[0135] [1] Shen Long, Chen Wei. Application of cold anti-fog film in multi-layer co-extrusion film[J]. Meat Industry, 2016, (08): 51-53.

[0136] [2]RATHER J A, AKHTER N, ASHRAF Q S, et al. A comprehensivereview ongelatin: understanding impact of the sources, extractionmethods, andmodifications on potential packaging applications.Food Packaging and ShelfLife,2022,34:100945.

Claims

1. An anti-fog high barrier food preservative film, characterized in that: The food preservative film is a multi-layer structure, consisting of a base layer, two surface spray self-assembly layers and two coating layers; The base layer is arranged in the middle of the thickness direction of the cling film, the two surface spray self-assembled layers are arranged on the two surfaces of the base layer respectively, and the two coating layers are arranged on the outer surfaces of the two surface spray self-assembled layers respectively; The base layer is a low-density polyethylene film layer, which is formed by placing orange peel particles in a low-density polyethylene solution for casting. The particle size of the orange peel particles is 50-100 μm, and the amount of the orange peel particles added is 5-8% of the weight of the low-density polyethylene. The surface spray self-assembled layer is prepared by spraying a sodium alginate solution containing tartaric acid on a substrate layer by electrostatic spraying to obtain a sodium alginate spray surface; then spraying a chitosan solution containing tartaric acid on the sodium alginate spray surface by electrospraying, and then drying to obtain a surface spray self-assembled layer; in the sodium alginate solution, the solvent is water, the weight percentage of sodium alginate is 3-5%; the amount of tartaric acid added is 1-2% of the weight of sodium alginate; in the chitosan solution, the solvent is a mixture of acetic acid and water in a volume ratio of 7:4, the weight percentage of chitosan is 1-2%, and the amount of tartaric acid added is 1-2% of the weight of chitosan; The coating layer is obtained by applying a gelatin solution containing orange peel water extract, lemon peel water extract and glutamine transaminase on a surface, spraying a self-assembled layer and drying it, wherein the weight ratio of the orange peel water extract, lemon peel water extract and glutamine transaminase is 15-20:5-8:1; in the gelatin solution, the solvent is water, the weight percentage of gelatin is 5-6%, and the amount of the orange peel water extract added is 3-5% of the weight of the gelatin.

2. The anti-fog high barrier food preservative film according to claim 1, characterized in that: The added amount of the orange peel particles is 6% of the weight of the low-density polyethylene.

3. The anti-fog high-barrier food preservative film according to claim 2, characterized in that: In the sodium alginate solution, the solvent is water, and the weight percentage of sodium alginate is 4%; the added amount of tartaric acid is 1.5% of the weight of sodium alginate; in the chitosan solution, the solvent is a mixture of acetic acid and water in a volume ratio of 7:4, the weight percentage of chitosan is 2%, and the added amount of tartaric acid is 1.5% of the weight of chitosan.

4. The anti-fog high-barrier food preservative film according to claim 3, characterized in that: The weight ratio of the tangerine peel water extract, lemon peel water extract and glutamine transaminase is 18:6:

1. In the gelatin solution, the solvent is water, the weight percentage of gelatin is 6%, and the added amount of the tangerine peel water extract is 4% of the weight of the gelatin.

5. The anti-fog high-barrier food preservative film according to claim 4, characterized in that: In the surface spray self-assembled layer, the weights of sodium alginate and chitosan are consistent; the thickness ratio of the base layer, the surface spray self-assembled layer and the coating layer is 3:1:

1.

6. The anti-fog high barrier food preservative film according to claim 1, characterized in that: The preparation method of the tangerine peel water extract is as follows: wash and chop the tangerine peel, add water according to the weight ratio of tangerine peel to water of 1:10, soak overnight, decoct twice, each time for 1 hour, filter and combine the filtrate, concentrate the filtrate to an extract, and then freeze-dry the extract into powder.

7. The anti-fog high-barrier food preservative film according to claim 1, characterized in that: The preparation method of the lemon peel water extract is as follows: wash and chop the lemon peel, add water according to the weight ratio of lemon peel to water of 1:10, soak overnight, decoct twice, each time for 1 hour, filter and combine the filtrate, concentrate the filtrate to an extract, and then freeze-dry the extract into powder.

8. A method for preparing an anti-fog high-barrier food preservative film, characterized in that: The food preservative film is an anti-fog high-barrier food preservative film as claimed in any one of claims 1 to 7; the preparation method comprises the following steps: (1) dissolving low-density polyethylene in chloroform to form a solution of 3 to 5 g / L, adding the orange peel particles and mixing them thoroughly, casting them into a culture dish, and drying them in a forced air dryer at 55° C. for 6 hours to obtain a base layer; (2) spraying the sodium alginate solution containing tartaric acid onto one surface of the substrate layer by electrostatic spraying, with a voltage of 20 KV, an injection speed of 1 mL / h, and a needle size of 25G, to form a sodium alginate spray surface, and then spraying the chitosan solution containing tartaric acid onto the sodium alginate spray surface by electrospraying, with a voltage of 18 KV, an injection speed of 0.5 mL / h, and a needle size of 18G, to form a surface spray self-assembled layer; and then treating the other surface of the substrate layer in the same manner to obtain another surface spray self-assembled layer; (3) The orange peel water extract, lemon peel water extract, glutamine aminotransferase and gelatin are dissolved in water, and then uniformly coated on the outer surfaces of the two surface spray self-assembled layers respectively, and then dried in a forced air dryer at 55° C. for 6 hours to obtain two coating layers.

9. The method for preparing an anti-fog high-barrier food preservative film according to claim 8, characterized in that: In the surface spray self-assembled layer, the weights of sodium alginate and chitosan are consistent; the thickness of the base layer is 0.03 mm, and the thickness ratio of the base layer, the surface spray self-assembled layer and the coating layer is 3:1:

1.

10. Use of the anti-fog high-barrier food cling film according to any one of claims 1 to 7 or the anti-fog high-barrier food cling film prepared according to the preparation method according to claim 8 or 9 as a food cling film, wherein the food comprises peaches.

Citation Information

Patent Citations

  • A biaxially oriented polyethylene heat-sealing anti-fog film and its preparation method

    CN113119567B

  • Method for preparing edible wrapping film

    CN101885920A

  • Polyethylene mould-proof fresh-keeping film and preparation method thereof

    CN107573624A

  • Preparation method of anti-fog anti-softening packaging material for fried potatoes

    CN108794859A

  • Chitosan / polyvinyl alcohol composite multifunctional microporous active packaging material as well as preparation method and application thereof

    CN116751386A